Management of Training Outcomes for Paud Teachers through Online Learning to Improve Skills Using Learning Media - Maryati Maryati; Iim Wasliman; Deti Rostini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research is motivated by the problem of mastering the use of IT as a learning medium. Skill is a skill that is learned by training, in line with regulation Number 74 of 2008. Changing times, the development of science is coupled with the Covid-19 world outbreak, so that it requires teachers to be skilled at using IT media as an effective and efficient learning tool. This study aims to find out the description and description of planning, skills, implementation, barriers, evaluation, from the results of basic level training for PAUD teachers through online learning to improve skills in using learning media. The method used is descriptive method with a qualitative approach and data collection techniques through interviews, observations, and documentation. Grand theory of George Tery. The object of research in two schools, namely KB Rumah Bintang and Melati Kota Bandung. Based on the research findings, it was obtained that a) the planning carried out included online media learning training teachers because there were already many online learning media b) teacher skills continued to be improved to create interactive learning with online learning processes c) the implementation of training was very helpful according to relevant needs d) the obstacles in each school are different, the biggest factors are cost and opportunity e) evaluation of efforts to maintain competence and improve teacher performance f) the findings of the training have a very significant impact in terms of knowledge, skills and the application of the online learning process. The conclusion is that the management of PAUD teacher basic level training through online learning to improve the skills of using learning media has a positive and significant contribution.